Thermal performance by the traditional roof section in Bangladesh - Rashid, Rumana (2007)
Traditional House represents the heritage of Bangladesh and also reflects traditional forms and values, fundamental to the culture of the people of the country. It possesses distinct characteristics with regards to planning, use of materials and location. Like urban architecture, traditional house is also subject to change but in Bangladesh the traditional houses have clung to tradition. It has not really changed until recently. For centuries traditional houses has been using locally available materials. It is only from the late 19th century that the traditional houses began to change in the use of materials. Traditional architecture in Bangladesh was largely built without formally trained professionals. Buildings were built by construction workers. The full planning concept has been developed by the people according to needs. The traditional house has been changed along with time to fulfill the demand of the user. At the same time planning concept remains constant. The different kinds of houses were developed in different climatic regions of Bangladesh such as mud houses, bamboo houses, stilts houses and timber houses. The stilts house was selected for this research study. The reason will be discussed at the end of this chapter.